In Vivo Vascularization of Cell-Supplemented Spider Silk-Based Hydrogels in the Arteriovenous Loop Model - Osterloh, Justus; Heltmann-Meyer, Stefanie; Trossmann, Vanessa T.; Cai, Aijia; Kulicke, Yvonne; Terörde, Klara; Sörgel, Celena; Lang, Isabell; Wajant, Harald; Scheibel, Thomas; Fey, Tobias; Steiner, Dominik; et al. (Biomimetics, 2025)
The goal of reconstructive surgery in treating tissue defects is to achieve a stable reconstructive outcome while minimizing donor site morbidity. As a result, tissue engineering has emerged as a key focus in the pursuit of this goal. One approach is to create a tissue container that can be preconditioned and later transplanted into the defect area. The characteristics of the matrices used in the tissue container are critical to this approach’s success. Matrices generated with recombinant, functionalized spider silk (eADF4(C16)-RGD) have been reported to be biocompatible and easy to vascularize. However, the effect of exogenously added proangiogenic cells, such as endothelial cells (T17b), on the vascularization process of matrices generated with this hydrogel in vivo has not been described yet. In this study, we implanted arteriovenous (AV) loop containers filled with a spider silk hydrogel consisting of an eADF4(C16)-RGD matrix and encapsulated, differentiated endothelial T17b cells producing the reporter protein TNFR2-Fc-Flag-GpL. The histological and µCT analyses revealed spontaneous angiogenesis and fibrovascular tissue formation in the container at 2 and 4 weeks post-implantation. The reporter protein was detected after 4 weeks. No severe immune response was observed. Altogether, this study demonstrates that cell-supplemented recombinant spider silk is a highly promising hydrogel to produce matrices for tissue engineering applications.
CRIS-Team Scopus Importer:2025-03-14
Keywords: recombinant spider silk; reconstructive surgery; tissue engineering; vascularization